DEVELOPMENT OF A LOCAL CURRICULUM FOR HEMP CULTIVATION TO DEVELOP PROFESSIONAL SKILLSFOR PRATHOM SUKSA 5 STUDENTS AT PAMAIUTID 4 SCHOOL - Sreebua, Supith (Journal of Social Science and Cultural, 2023)
The objective of research report have to 1) study of teaching and learning 2) create and develop the efficiency of local curriculum 3) study the results of local curriculum using and 4) evaluate satisfaction of local curriculum for hemp cultivation to develop professional skills For Prathomsuksa 5 students, Pamaiuthit 4 School. It is research and development. The target groups were 29 students in grade 5/3 of PamaiUthit 4 School in the second semester of the academic year 2022. Independent variables were local curriculum. Dependent variables were learning achievement, performance behavior and satisfaction. The duration of the trial was 18 weeks. Research tools include local curriculum. Achievement test observational form and satisfaction questionnaire data analysis using means standard deviation independent t-test and content analysis, research resultsfound that.1) The condition of teaching and learning teachers must focus on occupational kills, apply knowledge in life. Some students have poor reading, writing, and media backgrounds, lacking group work skills. and not interested in agriculture. 2) Creating a local curriculum was found that Principles and Reasons, Vision, Objectives of the Program Course Objectives course description course structure learning content Teaching and Evaluation. Processes The content is divided into small units, 4 learning units, 18 plans. The efficiency of curriculum their E1/E2 values ​​were 83.36/82.00, higher than the specified criteria of 80/80. 3) Results of curriculum trials, there were 27 students who passed the criteria, representing 86.48 % of the achievement comparison. Learning after school is higher than before. Statistically significant at the 0.05 level. The performance behavior was at the highest level ( = 23.12, S.D. = 1.07) 4) Teachers were satisfied at a high level ( = 4.10, S.D. =0.14).